The Effect of Waste Management Policies, Community Participation, and Waste Treatment Technology on Environmental Pollution Levels in West Java - Yamtana, Yamtana; Duha, Tobias; Riduan, Akhmad; Sabir, Muhammad; Aprianto, Muchammad Chusnan (West Science Interdisciplinary Studies, 2023)
This study investigates the intricate interplay of social support, cultural factors, social norms, and the spread of infectious diseases through a comprehensive Structural Equation Model (SEM). Utilizing a sample representative of the population, the research explores the unexpected positive relationship between social support and disease transmission, alongside the robust connections of cultural factors and social norms. The findings underscore the importance of understanding sociocultural dynamics in shaping health-related behaviors. Recommendations for tailored interventions and considerations for public health strategies are discussed, offering insights that contribute to the evolving discourse on infectious disease prevention.